Analisis Kriminologi Terhadap Penyeludupan Pakaian Bekas (Studi Kasus Wilayah Hukum Polres Indargiri Hilir): Universitas Islam Riau - Abdul Munir; Risky Widarso (UIR PRESS, 2018)
This study aims to determine the factors causing people’s purchasing power against illegally used clothing in Indragiri Hilir Regency is high enough and to know the prevention effortsof illegal second-hand clothing in the community of Indragiri Hilir Regancy. Metode of this study was descriptive survey. This research is located in Legal Police Of Indragiri Hilir. Key informant in this research is Invisible Criminal Polres Indragiri Hilir and Customs. While the informants in this study are observation, interview and documentation. The results showed that the factors causing people’s purchasing power againts illegally used clothing in Indragiri Hilir Regency is quite high because of the community we do not care whether the cloting bought illegally or not is important is cheap and quality and society is not shy buy or use second hand products abroad especially used illegal gear. Efforts to prevent teh circulation of illegal second-hand clothing in the community of Indragiri Hilir Regency are : preventive that is supervision through marine patrol, and repressive that is making arrest or action while pre-emptive efforts have never been done.